O FETICHISMO DA PROLETARIZAÇÃO NA AGRICULTURA: uma análise da produção de soja em Balsas/MA - BOTELHO, Raimundo Edson Pinto (2017)
The sociometabolism of capital has created relations of production in the Maranhão countryside that has been characterized by the reproduction of models of dependent development, materialized in the production of agricultural commodities. These relationships are based on the modernization of agriculture, use of capital and exploitation of the workforce. These relationships are based on the modernization of agriculture, use of capital and exploitation of the workforce. At the same time as these relations of production promote the deterritorialization of peasant agriculture, they transform part of the peasants into temporary salaried workers . Thus, the objective of this study is to analyze the fetishism of proletarianization in ag riculture in a context of deepening of capital in the countryside, on the one hand, with agribusiness policies, based on the production of agricultural commodities, the prevalence of financial capital On productive capital and, on the other hand, the workers' struggle in a conjuncture of the crisis of Marxism, of the institutions of the working class and of social struggles. As a course, in addition to the references of historical materialism and exploration of secondary data, visits were made to the soybean production units alongside representatives of the rural workers' unions of Balsas. Thus, as a conclusion, it was found that the advance of capital with soybean production was not sufficient to create a broad process of proletarianization in agriculture along the lines of that existing with factory workers and the tertiary sector, since the Agricultural activity of soy production is temporary, and rural workers have failed to conquer labor and social security rights like those of the core of the proletaria t. In this way, the overvaluation of agribusiness and rural wage labor, to the detriment of family-based peasant production relations, has resulted in fetishization of proletarianization in agriculture, since, in addition to temporary work, low remuneration, overexploitation, slave labor, rural workers have fragile political organization. This fact, in addition to weakening the struggle, allows the even more significant advance of commodified agriculture and the retreat of familybased peasant agriculture.